A study on the fluoride content of commercially available ready-to-drink green teas - Silva, Juan Rafael Antonio Gerardo S.
Green tea is proven to contain fluoride, which is known to possess anti-cariogenic properties but can cause dental fluorosis in high amounts. However, it is not known whether these green teas still contain fluoride after being processed into their ready-to-drink state. For this reason, the researchers were urged to investigate whether they contain fluoride or not, and if they do contain fluoride, the researchers wanted to find out the amount in parts per million (ppm).This study aims to determine the fluoride content of commercially available ready-to-drink green teas since knowing whether these green teas contain fluoride may shed some light regarding its role in oral health, in term or caries incidence and fluorosis. Five different brands of commercially available ready-to-drink green teas had undergone Ion Selective Electrode Method to determine the amount of fluoride in parts per million. The data were analyzed using t-test in the SPS software with the p-value set at 0.05. The results of the study have shown that all five brands contain fluoride. C2 Lite has a mean fluoride content of 0.2540 ppm, Lipton has 0.5260 ppm, One has 1.7220 ppm, Pokka has a mean fluoride content of 0.4040 ppm and Unif has 1.900ppm.